2016
DOI: 10.1093/deafed/enw069
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Understanding in Preschool Children with Mild-to-Severe Hearing Loss

Abstract: Deaf and hard of hearing school-aged children are at risk for delayed development of emotion understanding; however, little is known about this during the preschool years. We compared the level of emotion understanding in a group of 35 4–5-year-old children who use hearing aids to that of 130 children with typical hearing. Moreover, we investigated the parents’ perception of their child's level of emotion understanding. Children were assessed with the Test of Emotion Comprehension. Parents were presented with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 49 publications
(68 reference statements)
1
8
0
Order By: Relevance
“…These findings may suggest that deaf children have a delay in emotion recognition in the early years. However, a recent study by Laugen, Jacobsen, Rieffe, and Wichstrøm (2016) found comparable emotion recognition performance in 4-5-year-old hearing and deaf children with mild-severe hearing loss, who may have better auditory access to conversations about emotions. It is possible that some deaf children are disadvantaged in developing emotion recognition abilities because emotion vocalisations, and/or rich exposure to language is important for learning about emotions.…”
Section: Emotion Recognition In Deaf Childrenmentioning
confidence: 91%
“…These findings may suggest that deaf children have a delay in emotion recognition in the early years. However, a recent study by Laugen, Jacobsen, Rieffe, and Wichstrøm (2016) found comparable emotion recognition performance in 4-5-year-old hearing and deaf children with mild-severe hearing loss, who may have better auditory access to conversations about emotions. It is possible that some deaf children are disadvantaged in developing emotion recognition abilities because emotion vocalisations, and/or rich exposure to language is important for learning about emotions.…”
Section: Emotion Recognition In Deaf Childrenmentioning
confidence: 91%
“…To date, few articles have been published investigating how hearing aids influence interindividual perception. One test of emotion understanding with a study of 4- to 5-year olds found that hearing-impaired children wearing hearing aids exhibit levels of emotion understanding equivalent to that observed with normal-hearing children ( Laugen, Jacobsen, Rieffe, & Wichstrøm, 2016 ). In contrast, on tests of emotion identification, hearing aid users generally have more difficulty than listeners with normal hearing.…”
Section: Interventionsmentioning
confidence: 99%
“…A possible explanation for this may be the easy access to early intervention as well as sign language tuition for parents of DHH children in Norway, which may, in turn, lead to better communication skills about emotions between parents and DHH children. Laugen, Jacobsen, Rieffe, and Wichstrom (2017) found that parents of preschool children with hearing loss were more accurate in estimating their child's emotion understanding than parents of TH children. The parents' more accurate estimation of their children's emotion understanding (Laugen et al, 2017) may have contributed to the higher level of agreement on emotional problems found in this study…”
Section: Discussionmentioning
confidence: 92%
“…Laugen, Jacobsen, Rieffe, and Wichstrom (2017) found that parents of preschool children with hearing loss were more accurate in estimating their child's emotion understanding than parents of TH children. The parents' more accurate estimation of their children's emotion understanding (Laugen et al, 2017) may have contributed to the higher level of agreement on emotional problems found in this study…”
Section: Discussionmentioning
confidence: 92%